Eksistensi Teori – Teori Pemidanaan Terhadap Pidana Hukuman Mati Di Indonesia - Valentino, Josep; Hariyanto, Diah Ratna Sari (KOLONI, 2025)
The Out of all the criminal penalties that are now in place, the death sentence is the harshest. The death penalty does, in fact, provide legal justification for the practice. But the death penalty has drawn criticism from a number of quarters or requirements that must be satisfied before it may be applied. The state as an institution responsible for maintaining order requires it to take appropriate steps. Criminal is a difficult choice in tackling crime. This is what causes the criminal law to be said to be like a double-edged sword, because in addition to protecting the public it also injures those suspected of committing a crime. With the existence of sentencing theories, sentencing will be more appropriate and fair based on the weight of the crimes committed and the sanctions that will be given to the perpetrators.